Вплив ослаблення звуку у атмосфері на просторову мінливість спектрів акустичного випромінювання БПЛА - Білюк, В. В. (ХНУРЕ, 2021)
An important role in the technology of detection and recognition of UAVs is played by the spectra of acoustic radiation, which in the process of observation undergo significant changes even from the same aircraft. The reasons for the weakening and degradation of the UAV acoustic radiation spectra are analyzed.
Keywords: БПЛА; виявлення БПЛА